Comparison of Lipid Profiles from Cord Blood Of Appropriate and Small for Gestational Age Babies in a Tertiary Care Hospital: A Case-control Study - Vishwanath Machakanur; Narayan V Nayak; Naresh T Pavaskar; Malatesh Undi; A Rachana (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Hyperlipidemia and its complications are common health issues in the current era with multifactorial in origin. Foetal malnutrition results in neuroendocrine, pancreatic, and adipose tissue dysfunction, ultimately increasing food intake and decreasing energy utilisation. It leads to an increase in adiposity and insulin resistance and ultimately increase adult diseases in later life. Aim: To compare the lipid profiles of Small for Gestational Age (SGA) and Appropriate for Gestational Age (AGA) babies. Materials and Methods: This was a case-control study was conducted in the Department of Pediatrics, Obstetrics and Gynecology of Karwar Institute of Medical Sciences, Karwar, Karnataka, India over a period from (December 2020 to March 2021). A total of 133 deliveries were recruited randomly and babies were divided into cases including those small for gestational age & controls including those appropriate for gestational age. Data was analysed and described using descriptive (mean, standard deviation, and range) and inferential statistics (students' t-test). Results: There were 99 appropriate for gestational age (AGA) and 34 small for gestational age(SGA) babies studied. This study found that SGA-babies had statistically significantly lower gestational age(Mean 37.50 ± 2.77 weeks) at birth compared to AGA-babies (Mean 38.55±1.11 weeks) t=-2.584, p=0.012. The mean Total Cholesterol (TC) level (63.62±40.48 mg/dL) was higher in SGAbabies compared to AGA-babies(48.69±2.29 mg/dL) and this difference was statistically significant (p-value=0.007). The mean high density lipoprotein (HDL) levels of SGA and AGA babies were comparable with no statistical significance (21.82±13.26mg/ dL of SGA; 21.4914.64mg/dL of AGA; p-value 0.907). The mean very low density lipoprotein (VLDL) level (17.1125.35 mg/dL) was higher in SGA-babies compared to AGA-babies (9.47±9.35 mg/ dL) and this difference was statistically significant (p-value 0.05). Conclusion: Levels of all lipids were found to be higher in SGAbabies than in AGA-babies.